2007
DOI: 10.1158/0008-5472.can-07-1161
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interplay of p53 and Mus81 in DNA Damage Responses and Cancer

Abstract: Mus81 plays an integral role in the maintenance of genome stability and DNA repair in mammalian cells. Deficiency of Mus81 in human and mouse cells results in hypersensitivity to interstrand cross-linking (ICL) agents and elevated levels of genomic instability. Furthermore, Mus81-mutant mice are susceptible to spontaneous lymphomas. The role of cellular checkpoints in mediating the phenotypes observed in Mus81-deficient cells and mice is currently unknown. In this study, we have observed increased activation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…35 Mus81-deficient mouse embryonic fibroblasts displayed an elevated level of p53 in response to MMC, and p53 inactivation rescued the ICL sensitivity of Mus81-deficient cells at the expense of increased genomic instability. 36 In this study, our results evidenced an elevated expression of phosphorylated p53 in Mus81-suppressed MCF-7 cells after cisplatin treatment, but the Bcl-2 expression changed in the opposite direction. The results were consistent with the recent study in HCC cells.…”
Section: Discussionsupporting
confidence: 58%
“…35 Mus81-deficient mouse embryonic fibroblasts displayed an elevated level of p53 in response to MMC, and p53 inactivation rescued the ICL sensitivity of Mus81-deficient cells at the expense of increased genomic instability. 36 In this study, our results evidenced an elevated expression of phosphorylated p53 in Mus81-suppressed MCF-7 cells after cisplatin treatment, but the Bcl-2 expression changed in the opposite direction. The results were consistent with the recent study in HCC cells.…”
Section: Discussionsupporting
confidence: 58%
“…Mice homozygous for the Mus81 Δex3-4 mutation showed no expression of Mus81 protein, and displayed elevated levels of spontaneous genomic instability and cancer predisposition [11]. While the cause for the lack of tumorigenesis in Mus81 Δex9-12 mutant mice is still not clear, inactivation of p53 in Mus81 Δex3-4/Δex3-4 mice rescued their MMC hypersensitivity and exacerbated their genomic instability and tumorigenesis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Mus81 was found to interact with p53 and checkpoint genes such as Cds1 ⁄ chk2 and Rhp51 ⁄ Rad51. (17)(18)(19) Recently, Mus81 has also been shown to be required in the survival of telomerase-negative cancer cells by alternative lengthening of the telomeres pathway.(20) Also, the single nucleotide polymorphisms of Mus81 were found to be associated with an increased risk of developing breast cancer.(21) Although these studies have indicated the potential role of Mus81 in human malignancies, the evidence for its expression pattern in human malignancies is still limited. (22,23) In a previous study, we have documented the decrease of Mus81 expression in human hepatocellular carcinoma (HCC) tissues and its association with metastasis and poor prognosis, which provided the first evidence for the expression pattern and potential role of Mus81 in human malignancy.…”
mentioning
confidence: 99%
“…Moreover, Mus81 was found to interact with p53 and checkpoint genes such as Cds1 ⁄ chk2 and Rhp51 ⁄ Rad51. (17)(18)(19) Recently, Mus81 has also been shown to be required in the survival of telomerase-negative cancer cells by alternative lengthening of the telomeres pathway. (20) Also, the single nucleotide polymorphisms of Mus81 were found to be associated with an increased risk of developing breast cancer.…”
mentioning
confidence: 99%